A large retropharyngeal lipoma causing upper airway obstruction in a 64-year-old patient: case study - Savitskaya, Tatyana; Kutaj, Aleksandra; Savitski, Kiryl; Hatala, Ignacy; Sarata, Maria Teresa; Prusinowski, Filip; Stabrawa, Magdalena; Wiczkowski, Dawid (Journal of Education, Health and Sport, 2025)
Introduction and Purpose Retropharyngeal lipomas are extremely rare benign mesenchymal tumors that often remain asymptomatic until reaching a considerable size. Due to their deep anatomical location, they may cause progressive airway or digestive tract compression, leading to potentially life-threatening symptoms. The purpose of this case report is to present a large retropharyngeal lipoma causing upper airway obstruction, outline the diagnostic difficulties, and describe the surgical management. Material and Methods A 64-year-old male patient with a one-month history of worsening dyspnea, dysphagia, and orthopnea was evaluated using computed tomography (CT) and magnetic resonance imaging (MRI). Imaging studies assessed the size, boundaries, and anatomical relationships of the lesion. The patient underwent planned tracheostomy followed by complete transpharyngeal surgical excision of the tumor. Histopathological examination was performed postoperatively. Results CT and MRI revealed a well-defined encapsulated fatty mass in the retropharyngeal space measuring up to 130 × 83 × 31 mm, leading to narrowing of the pharyngeal lumen and upper laryngeal segment. The lesion displaced adjacent cervical vascular structures and compressed the airway. Complete surgical removal was achieved without intraoperative complications. The postoperative course was uneventful, with successful decannulation on day 10. Histopathology confirmed a non-infiltrating lipoma with focal fibrolipomatous features. Conclusion Although benign, retropharyngeal lipomas may cause significant airway obstruction and require timely diagnosis and management. Precise radiological evaluation is essential to determine tumor extent and guide the surgical approach. Complete excision remains the treatment of choice, ensuring symptom resolution and minimizing the risk of recurrence or complications.